MORPHOLOGICAL SUBSTANTIATION OF CRITERIA OF PREDICTION OF CLINICAL COURSE OF GENERALIZED PERIODONTITIS - Hasiuk, N.V.; Levandovsky, R.A.; Borodach, V.O.; Klitynska, O.V. (World of Medicine and Biology, 2018)
In the article the ways to optimize the diagnostic process periodontal patients through an integrated cytology. The results make it possible development of morphological algorithm for evaluation of patients younger patients with generalized periodontitis of varying severity. Application of the proposed algorithm survey, which includes the study of cellular structure periodontal pockets and immunohistochemical profile of cell infiltration of the lamina propria gums in periodontitis, and morphological changes cytospeciefic epithelium provides an opportunity to supplement the existing arsenal of conventional diagnostic methods in periodontology more accurate and highly specific, and offer a number of morphological criteria prognostic clinical course of nosological unit.